Full‐scale demonstration testing of hexavalent chromium reduction via stannous chloride application. Issue 2 (24th April 2019) - Henrie, Tarrah; Plummer, Sarah; Orta, John; Bigley, Steve; Gorman, Craig; Seidel, Chad; Shimabuku, Kyle; Liu, Haizhou
Abstract : The best available technologies for hexavalent chromium [Cr(VI)] treatment can be cost prohibitive and operationally complex. Direct stannous [Sn(II)] chloride application to reduce Cr(VI) to trivalent chromium is an alternative treatment approach that could substantially decrease treatment costs. A full‐scale demonstration was conducted at the Coachella Valley Water District to investigate the ability of Sn(II) to reduce Cr(VI) in a chlorinated groundwater system. An average Sn(II) dose of 0.5 mg‐Sn/L, which corresponds to 7.3 times the stoichiometric dose ratio for Cr(VI) reduction, was able to maintain Cr(VI) at <10 μg/L throughout the distribution system over a 30‐day period. Tin (Sn) and chromium (Cr) concentrations decreased with increasing distance from stannous feed locations, suggesting accumulation in the distribution system. Distribution system pipe‐scale analysis after the demonstration found the presence of Sn and Cr in pipe scales; however, minimal Sn and Cr release was observed during main flushing at the end of the demonstration.